Real-Time PCR Assay for Rapid and Simultaneous Detection of vanA and vanB Genes in Clinical Strains - Hanane Zerrouki (MDPI AG, 2021)
Here, we develop a robust and sensitive real-time PCR assay which allows the simultaneous detection of vanA and vanB genes using common primers. The system was designed using the Primer3 online software. The specificity of primers and probes was first checked by in silico PCR and by BlastN analysis. The genomic DNA of 255 bacterial isolates, including Enterococcus spp., Gram-negative, and Gram-positive strains, as well as a collection of 50 stool and 50 rectal swab samples, were tested to evaluate the specificity of the new real-time PCR (RT-PCR) system. The results of the designed RT-PCR were 100% specific and 100% positive on tested vancomycin resistant isolates harboring either the vanA or vanB gene. RT-PCR assays were negative for all other bacterial species tested including vancomycin-sensitive Enterococci and Enterococcus strains harboring vanC genes. The limit of detection of vanA and vanB genes by RT-PCR assay was 47 CFU/mL and 32 CFU/mL, respectively. The rapid and accurate detection of vancomycin-resistant Enterococci is the cornerstone for minimizing the risk of nosocomial transmissions and outbreaks. We believe that this assay will strengthen routine diagnostics and surveillance programs.